An interprofessional day of hi-fi simulation of Family and Domestic Violence with midwifery students and social work students - Kuliukas, Lesley; Oehlers, K.; Berlingeri, J. (2017)
An interprofessional simulated learning day with standardized patients (hired actors) was held for student midwives and student social workers in a simulated hospital ward in response to a situation involving Family and Domestic Violence (FDV). Two scenes were pre-written and an unplanned scene was also improvised. Initial evaluation of the session was conducted by questionnaire, with capacity for quantitative responses using a five point Likert Scale and qualitative replies to questions via textbox. A focus group with the six midwifery students offered an opportunity to provide feedback the following week. Overall findings suggest that students found the simulation a realistic, valuable and safe experience. Student midwives felt less prepared than the social work students and some were confronted by the realism when faced with a scene of FDV; all valued the interprofessional experience and found it useful to discover the role of their professional counterparts in responding to FDV.